Capacity of Notational Systems:Some New Formulae for Calculations - Hussain, Shabahat (Journal of Information and Knowledge, 1991)
As the digits used to build the notational system of any scheme are limited and the concepts to be represented by them are fairly large, it is always interesting to find out the number of subjects that can be accommodated in a scheme i.e. the capacity of notation. This exercise has meaning not only for future schemes of classification but also for existing schemes. With this view, certain formulae which may be useful for calculating the capacity of non-faceted and faceted notational systems, have been worked out. A small programme was developed for computing the capacity of different types of notational systems. An analysis of the data obtained reveals a far greater capacity of faceted notation over non-faceted notation. Concludes that the capacity, in general, increases with the gradual addition of digits in a class number(i.e. d), and, in particular, with the number of facets in a class number (i.e. n). Demonstrates mathematically that it is not advantageous to increase the number of digits in a single facet to nd.